Wykorzystanie nowoczesnych metod i technik zarządzania w polskich i rosyjskich przedsiębiorstwach - analiza porównawcza - Cyfert, Szymon; Krzakiewicz, Kazimierz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This study is aimed at presenting the results of research on the use of modem management methods and techniques in Polish and Russian enterprises. The research results presented herein represent a fraction of a wider project aimed at identifying changes taking place in the management process of businesses operational in Poland, Russia, Romania, and Hungary, which focuses on: • identification of changes taking place in management system, • analysis of use of modern management methods and techniques, • assessment of structural solutions implemented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 263-272